Measurement of thermal cycles in the weld heat affected zone of mild steel - Coward, M. D.; Apps, R. L. (College of Aeronautics, 1967)
The thermal cycles in the mild steel parent plate adjacent to a bead on plate weld have been measured for heat inputs of 108, 54 and 42 kJ/inch, by means of embedded thermocouples connected to high response automatic recorders. The results show that decreasing the heat input increases the cooling rate and decreases the width of the heat affected zone. For thermal cycles in which the peak temperatures reached 900°C or above, two points of inflection have been noted in the temperature ranges 400° - 600°C and 950° - 1200°C. The inflection in the lower temperature range, which has been observed by other workers, has been attributed to latent heat from the exothermic transformation of austenite to ferrite. The higher inflection point, not previously reported, has been tentatively related to the solidification in the weld pool and the release of the latent heat of fusion.